Durable and long-lasting transparent anticorrosive films for copper substrates using mesoporous silica nanocontainers loaded with corrosion inhibitor. Issue 1 (13th October 2021) - Matsuzaki, Masaki; Yamauchi, Yusuke; Nakamura, Satoshi; Sato, Tomoya; Urata, Chihiro; Hozumi, Atsushi
Abstract: We have developed functional films capable of retaining anticorrosive properties even after severe mechanical damage which directly exposes the metal surface to corrosive environments. It was found that functional films prepared by simply dispersing mesoporous silica-nanocontainers loaded with a corrosion inhibitor, tolyltriazole, in a commercially available aqueous polyurethane solution could effectively prevent the corrosion of copper substrates. Even after cutting of the films and submersion in aqueous sodium chloride, no serious oxidation of the damaged areas was observed for up to four months. The transparency of the resulting polyurethane films remained almost unchanged with or without the addition of MPS-NCs/TTA.